2020
DOI: 10.2174/1871530319666190529090517
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dyslipidemia and Preterm Birth: A Prospective Cohort Study in The North of Iran

Abstract: Background: Dyslipidemia is recognized as an important factor in the incidence of Preterm Birth (PTB). The early diagnosis of factors affecting PTB is important in the reduction of maternalneonatal complications; therefore, we aimed to evaluate the association between dyslipidemia and PTB in women from the Guilan province of Iran. Method: The current investigation was a prospective cohort study on 378 pregnant women in Rasht city (Guilan province), during 2018-2019. Samples were randomly selected among pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results showed that among the lipid profiles evaluated, the predictive power of TG for PTB had an AUC = 0.833 (95%, CI 0.736–0.930), respectively. In addition, abnormal LDL concentrations increased the risk of PTB by twofold (P < 0.05) 25 .…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that among the lipid profiles evaluated, the predictive power of TG for PTB had an AUC = 0.833 (95%, CI 0.736–0.930), respectively. In addition, abnormal LDL concentrations increased the risk of PTB by twofold (P < 0.05) 25 .…”
Section: Discussionmentioning
confidence: 98%
“…Accumulation of cholesterol in macrophages can trigger pro-inflammatory signaling pathways ( 26 ). It is well-validated that pregnant women with hypercholesterolemia are associated with increased risk of PTB ( 2 , 3 , 32 ). Therefore, we hypothesize excessive cholesterol from the mother with hypercholesterolemia will be transported into the placenta and accumulate in macrophages, which will subsequently increase the inflammation, triggering PTB ( Figure 1 ).…”
Section: Presentation Of the Hypothesismentioning
confidence: 99%